ANALISIS KOMPETENSI PEDAGOGIK GURU DALAM PEMBELAJARAN PADA ANAK USIA 5-6 TAHUN - Juliana, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this research is to know the "Competence Pedagogy Master in Education in Children Ages 5-6 Years On ECD Light Lime Village Sungai Raya?" Method in this research is descriptive method with a form of qualitative research. Subjects in this study were teachers group B ECD Light Lime Village Sungai Raya, amounting to two people. Mechanical engineering data collectors which direct communication and direct observation. With a data collection tool that is sheet interviews, observation, and field notes. Interviews and direct observation that the efforts made to improve the pedagogical competence include organizing various aspects of development of children aged 5-6 years is to examine the ability, classify, identify prior knowledge and identify difficulties early childhood in accordance with the level of development and characteristics of learners it allowing playful learning activities can take place properly. Keyword: Pedagogic Competence Teachers, Education and Early Childhood. Â